Évolution - Riva, Zacarías M. de la 1972-; Díaz, Jesús ca. 20. Jh (Metrodome Distribution, 2016)
"French drama from film-maker Lucile Hadzihalilovic. Nicolas lives in a small village on a remote island in the middle of nowhere. This location is all he has ever known and the people around him, young women and boys his age, are the only people he has ever had contact with. When he discovers something mysterious on the beach he starts to question the motives of his mother and the other women who seem to be conducting strange experiments on the boy." [amazon.de]
Original: Frankreich, Belgien, Spanien 2015
Bildformat 2.35:1 (16:9)
Keywords: Film; DVD-Video